The Effect of Food Quality and Halal Labeling on Consumer Loyalty through Customer Satisfaction at McDonald’s West Jakarta Branch - Zaidan, Muhamad; Afrianita, Nina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the effect of food quality and halal labels on customer loyalty through customer satisfaction at the McDonald’s West Jakarta branch. The population in this study consisted of Muslim consumers who purchased products from the McDonald’s West Jakarta branch at least twice within six months and were aged between 17 and above 35 years old. The sampling method used was non-probability sampling, resulting in a total sample of 105 respondents. Data were analyzed using the Structural Equation Model (SEM) with SmartPLS. The results indicate that food quality and halal labels have a positive effect on customer satisfaction. Customer satisfaction also has a positive effect on customer loyalty. Furthermore, food quality and halal labels positively influence customer loyalty. Customer satisfaction acts as an intervening variable in the relationship between food quality, halal labels, and customer loyalty.